Studi Pengendalian Banjir Sungai Remu Kota Sorong Provinsi Papua Barat - Pramana, Yanuar Hendra; Harisuseno, Donny; Dermawan, Very (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2014)
Sorong City where is located in West Papua Province has often experiences flooding due to overflow of Remu River. This study aims to find the proper flood management alternatives through hydrology, hydraulic, and economy approach. Based on hydrology analysis with Log Pearson III method, the highest historical rainfall that ever occured is the rainfall with return period of 16 years, that is 224.2 mm. The HEC RAS 4.1. simulation results n value of 0.021 with relative error of 2.64%. The proper flood managements are dike and retarding basin and the both of the alternatives use return period of 25 years. Dike has been choosen as then proper alternative with total ranking of 0.53 based on priority scale determination using Analyrical Hierarchy Process method with technique, economy, and easy implementation considerations.Keywords: Flood, HEC RAS, Analytical Hierarchy Process, Dike, Retarding Barsin.